Postmodernist Transformations: Writing and Text - Ch V Zabolotnaya (RUDN Journal of Philosophy, 2013)
Postmodernism has created a very interesting, though a little amorphous concept network, which determines all postmodernism reflection and critical analysis of the previous types of philosophical discourse. The author represents one of the versions of categorical evolution in that part of postmodernism philosophy, which is closely connected with linguistics, semiotics, and literary studies. The category of writing, literature and text are interconnected into the chain of philosophical concepts developing in the framework of postmodernism.